Rational Use of Drugs in the Complex Treatment of Bronchobstructive Syndrome in Children - Bekchanov Bakhtiayr Gafurovich (Journal of Medical Genetics and Clinical Biology, 2024)
Treatment of biofeedback in children and the complex use of drugs, that is, each drug must be pathogenetically justified, taking into account the individual characteristics of the child, and also based on knowledge of the mechanism of their action and pharmacokinetics. It is necessary to have a complex effect on individual links in the pathogenesis of broncho-obstructive syndrome in many cases, which justifies the use of complex drugs with a combined mechanism of action. Thus, the treatment of biofeedback in children is a responsible task for the pediatrician, which consists in the rational selection of drugs.